Thoughts: premium pricing in B2C and B2B. Issue 4 (17th August 2018) - Hinterhuber, Andreas; Liozu, Stephan
Abstract This paper focuses on the topic of premium pricing in B2C and B2B environments. It clarifies the differences between luxury and premium pricing and offers relevant examples of both. It also identifies five trends that impact premium pricing strategies and that can serve as avenues for further research. To practicing managers, this paper offers guidance on the critical trends affecting premium pricing in the future.